Bee pollen as a food and feed supplement and a therapeutic remedy: recent trends in nanotechnology - Anjum, Syed Ishtiaq; Ullah, Amjad; Gohar, Faryal; Raza, Ghulam; Khan, Muhammad Ilyas; Hameed, Mehwish; Ali, Abid; Chen, Chien-Chin; Tlak Gajger, Ivana (Frontiers in Nutrition, 2024)
Pollen grains are the male reproductive part of the flowering plants. It is collected by forager honey bees and mixed with their salivary secretions, enzymes, and nectar, which forms fermented pollen or "bee bread" which is stored in cells of wax honeycombs. Bee pollen (BP) is a valuable apitherapeutic product and is considered a nutritional healthy food appreciated by natural medicine from ancient times. Recently, BP is has been considered a beneficial food supplement and a value-added product that contains about 250 different bioactive components. It contains numerous beneficial elements such as Mg, Ca, Mn, K, and phenolic compounds. BP possesses strong antioxidant, antiinflammatory, antimicrobial, antiviral, analgesic, immunostimulant, neuroprotective, anti-cancer and hepatoprotective properties. It is used for different purposes for the welfare of mankind. Additionally, there is a growing interest in honey bee products harvesting and utilization for many purposes as a natural remedy and nutritive function.In this review, the impacts of BP on different organisms in different ways by highlighting its apitherapeutic efficacy are described.